Comparative assessment of the state of digitalisation in higher education institutions - N. I. Aksenova; O. V. Usacheva; M. K. Chernyakov (Russian State Vocational Pedagogical University, 2024)
Introduction. Today, there is no unified approach to understanding the main areas of digitalisation in education, its types, and elements. It is relevant to explore approaches to assess the state of digitalisation, reducing the subjectivity of assessments, and relying on objective data. Aim. The present research aimed to systematise and expand the areas subject to digitalisation in universities and to describe an algorithm for assessing the level of digitalisation using public information posted on university websites. Methodology and research methods. The main research methods involved morphological analysis, index, and matrix and score-rating methods. On the basis of the morphological matrix, the rating of a higher education institution was formed as an integral assessment, taking into account the weight values of its spheres. Results. The results of the research include the developed methodology for scoring and rating the assessment of the state of digitalisation in higher education institutions. This methodology encompasses four spheres of digitalisation: management and information security, organisation of the educational process, organisation of extracurricular activities, and profiling. Within these spheres, various types of digitalisation are identified, and elements are defined for each type. Higher education institutions in the Novosibirsk Region are ranked and grouped into clusters (six levels) based on the calculated integral assessment of their digitalisation level. Scientific novelty. The current research contributes to the development of a scientifically based approach to assessing the state of digitalisation in higher education institutions for comparative analysis using public information. The data obtained confirmed the necessity for further digital development to establish a comprehensive profile of a digital university. Practical significance. The practical significance of the results lies in the possibility of different groups of stakeholders (applicants, students, university management, and authorities) using the developed methodology to assess the state of university digitalisation and make various decisions, including managerial decisions.